Process Description for PLC Program Design - Azmi, A.; Shukor, M.A.A. (International Journal of Integrated Engineering, 2009)
Process description is essential and vital for PLC Program development. Various types of process descriptions method had been introduced but Flowchart, Narratives, Grafcet and Heuristic are amongst the favourites due to the direct translation and smooth flow of process sequence. In the study undertaken it is found that the process description can be further improved by combining the Heuristics method with the Grafcet process description method. This improvisation will make the PLC program development become more efficient, reliable and effective.